Vak learning styles and listening skills development in seventh grade students in an institution in north of Guayaquil, school year 2020 – 2021 - Mejía Nieto, Stefanía Belén (2021)
This research work is designed to determine the dominant learning style of seventh grade students of Regular Basic Education in an educational institution in District 5 located in the center of the city of Guayaquil. Taking into account that the National Curricular Design (Ministry of Education, 2009) “considers human, cultural and linguistic diversity, expressed in the intercultural approach that characterizes it, and that it is manifested in the competences considered in the three educational levels and in the different curricular areas ”(p.5), it seeks to identify within the diversity in the ways of learning, which style is the dominant one in the students, in such a way, information is available to address the diversity of learning styles among students. Learning styles refers to how people tend to learn better according to their teaching- learning method to acquire knowledge. It is essential because each student learns individually and in a different way, either at her learning style or pace. The learning style helps teachers to be more successful in their teaching processes. One of the main common problems that currently arise in our country is that educational institutions do not evaluate the learning styles of students or provide teachers with the necessary tools for students to learn to organize the information they receive and thus promoting the ability to learn by strengthening their learning...........